A fondness for lexical teddy dears a contrastive analysis of Filipino adjectives and their English translations by senior high school students - Reyes, Darwin Z. (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/8580
Keywords: Vocabulary; Lexicography; Education research